Digital storytelling and performative memory: new approaches to the literary geography of the postcolonial city - Jordan, Spencer (Palgrave Macmillan, 2018)
Drawing on the outcomes of a research project, this chapter argues that digital storytelling can play a fundamental role in the reconceptualization of the digitally-mediated geographies of the postcolonial city. The chapter argues that the interaction between walking and storytelling, incorporating aspects of augmented reality and ludic gameplay, can be considered a new form of performative mapping. In this way, the chapter shows how digital storytelling can make a significant and innovative contribution to the spatial representations of memory, and, through that, engage directly with a deeper need for ‘home’ and ‘belonging’.